Peran Kepemimpinan Transformasional Kepala Sekolah Dalam Progam Gerakan Literasi Sekolah di SMA Negeri 1 Cibungbulang - Ima Rahmawati; hana lestari; Siti Ulfatul Hasanah; Ela Kusyanti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2023)
The school literacy movement (GLS) is an effort made by educational institutions related to increasing the awareness of students to read and write so that they will gain broader knowledge and insights. The purpose of this study was to describe the influence of the school principal's transformational leadership on the school literacy movement at SMA Negeri 1 Cibungbulang, Bogor Regency. The research method used is a type of literature study research. Data collection in this study was obtained by examining and then linking reading sources to problems in the research area with the transformational leadership contributions of school principals to the school literacy movement. The principal of SMA Negeri 1 Cibungbulang has strategies and efforts to support the GLS program, namely making literacy journals, procuring class libraries, geulis trees, class bulletin boards, and literacy ambassadors. The GLS program that is being implemented is able to motivate students to increase their interest in reading, to be able to make good use of time, especially with the Geulis tree program and class madding. Besides reading, students can imagine and be creative in expressing their ideas from something they read. This is proven to be able to eliminate boredom during literacy hours. Keywords: School Literacy Movement, Transformational Leadership